THE ARRIVAL OF MADURA TRADERS TO SUMBAWA BESAR (STUDY OF CULTURAL ASSIMILATION OF SUMBAWA BESAR COMMUNITY WITH MADURA TRADERS) - Amar, Syahrul; Rasyad, Abdul; Fetridawati, Fetridawati (Walasuji : Jurnal Sejarah dan Budaya, 2021)
This study described the history of the arrival of Madurese traders to Sumbawa Besar with a cultural assimilation process of Sumbawa Besar and Madurese communities. The purpose of this study was to find out the history of the arrival of Madurese traders to Sumbawa Besar, to find out the cultural assimilation process of Madurese and Sumbawa Besar communities, and to find out the impact of the assimilation between Sumbawa Besar and Madurese communities. This research was qualitative research. Data collection was done through direct observation, interviews, documentation, and literature study. The study result concluded that Madurese traders came to Sumbawa in the middle of 17th century through trading relation. In the middle of 20th century around 1920, several Madurese began to explore the land of Sumbawa Besar. The cultural character of open and democratic society made Madurese traders and Sumbawa’s people to assimilate easily. The assimilation process was carried out through social interaction, marriage, trade, and religious processes. The impact of the cultural assimilation of Sumbawa Besar and Madurese communities was shown by the establishment of a communication relationship between Sumbawa Besar and Madurese communities, the construction of a new community structure for the integrated of Sumbawa Besar community as Tau and Tana Samawa, and the construction of a new culture as Sumbawa’s culture requiring openness and tolerance.